Physiological and transcriptional response to heat stress in heat-resistant and heat-sensitive maize (Zea mays L.) inbred lines at seedling stage - De-Chuan Wu; Jia-Fei Zhu; Zhong-Ze Shu; Wei Wang; Cheng Yan; Shan-Bin Xu; De-Xiang Wu; Cheng-Yu Wang; Zhao-rong Dong; Genlou Sun (Protoplasma, 2020)

Ecological analysis of gamasid mites on the body surface of Norway rats (Rattus norvegicus) in Yunnan Province, Southwest China - Zhe Liu; Xian-Guo Guo; Rong Fan; Cheng-Fu Zhao; Ke-Yu Mao; Zhi-Wei Zhang; Yue Zhao (Biologia, 2020)

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

The effects of mesoscale oceanographic structures and ambient conditions on the catch of albacore tuna in the South Pacific longline fishery - Cheng Zhou; Pingguo He; Liuxiong Xu; Pascal Bach; Xuefang Wang; Rong Wan; Hao Tang; Yu Zhang (Fisheries Oceanography, 2020)
Albacore tuna ( Thunnus alalunga ) exhibit patchy concentrations associated with biological process at a wide range of spatial scales, resulting in variations in their catchability by fishing gears. Here, we investigated the association of catch variation for pelagic longlines in the South Pacific Ocean with oceanographic mesoscale structures (in horizontal dimension) and ambient conditions (in vertical dimension). The distribution of albacore tuna as indicated by catch per unit effort (CPUE) of longlines was significantly related to the presence of mesoscale structures, with higher CPUE found at locations closer to thermal fronts and with greater gradient magnitudes, as well as areas marked by peripheral contour line of the anticyclone indicated by Sea Surface Height Anomalies ~0.05 m. Surface mesoscale current velocity had the negative effect on the catch, probably as a result of decreased catchability by shoaling the hook depth. Vertical distribution of albacore in the survey region of South Pacific Ocean was hardly restricted by ambient temperature and oxygen concentration, though effect of ambient temperature was relevant and showed a negatively linear correlation with CPUE at the range of 20–24°C. On the contrary, albacore distribution was evidently dominated by the water depth and showed strong preference on water depth of 200 m, which was likely a representative feeding layer. The presence of prey resources and their accessibility by albacore revealed by mesoscale structures in the biological and physical processes, and catchability determined by the location of the baited hooks comprehensively contribute to the variability of catch.

Circadian gene Clock participates in mitochondrial apoptosis pathways by regulating mitochondrial membrane potential, mitochondria out membrane permeablization and apoptosis factors in AML12 hepatocytes - Shuhong Yang; Yanyou Liu; Yimei Guo; Rong Liu; Fang Qi; Xiaoxue Li; Hang Yu; Shuting Cheng; Zhengrong Wang (Molecular and Cellular Biochemistry, 2020)

Atorvastatin ameliorates depressive behaviors and neuroinflammatory in streptozotocin-induced diabetic mice - Zhang Hai-Na; Yu Xu-Ben; Tang Cong-Rong; Cao Yan-Cheng; Yang Fan; Xu Lei-Mei; Sun Ruo-Lan; Ye-Zi; Wang Ye-Xuan; Liang Jing (Psychopharmacology, 2020)